Perceived Symptoms of Depression, Anxiety and Stress amongst Staff in a Malaysian Public University: A Workers Survey - Mohd Rizal Abdul Manaf (MDPI AG, 2021)
Mental health conditions are a major part of workers’ health that predisposes to poor self-motivation for sustaining productivity. This study was aimed to determine the prevalence of depression, anxiety, and stress among staff in a Malaysian public university and its associated factors. A cross-sectional study was conducted among 459 staff from the Universiti Kebangsaan Malaysia (UKM) between April and June 2019. A questionnaire that consisted of items on socio-demographic and socioeconomic characteristics, employment description, lifestyle risk behaviors, personal medical history, and symptoms of depression, anxiety, and stress was administered to participants. Descriptive and inferential statistics were conducted using SPSS version 22.0. The prevalence of perceived symptoms of depression, anxiety, and stress among the respondents was 28.7%, 50.1%, and 14.8%, respectively. Over one-quarter (26.5%) of the participants presented symptoms of two or more mental disorders. Women, those aged less than 40 years old, and non-academic professionals were more likely to exhibit depressive symptoms, while those with medical conditions that required hospitalizations sustained anxiety symptoms. Perceived stress was more likely to be prevalent among staff with secondary education or less and smokers. Proactive support for staff needs to be offered in sustaining their emotional well-being.